KEWIRAUSAHAAN ISLAM1 (ISLAMIC ENTREPRENEURSHIP) DALAM PENDIDIKAN DAN PEMBINAAN PENGELOLAAN PERKOPERASIAN MAHASISWA - Bashith, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Islam is a comprehensive religion, including business gets the attention the Koran. Islam teaches the values of ethical, moral and spiritual life that serves as a guide life to its adherents, not least at the economic field. Lots of Islamic teachings so that Islamic people want to work hard for themselves be honest in business, and looking for a business from their own hand to do good deeds. Entrepreneurial can be said as people who fight against the competition in the field of economics, and whoever doing entrepreneur accordance with the norms of law, religion, and economics then he was included as a reliable entrepreneurs in carrying out the strategies and policies that have been implemented in the fields of economics, included in the category of people who want to seriously in the running life. Islamic entrepreneurship are required to have the strength and values who is able to uphold its business. Thus the study of Islamic entrepreneurship in education and management of student cooperatives be interesting to learn and do in order to continue its operations by giving attention to the principles of Islam. The teachings of Islam itself has taught the duty of man to always trying and praying in carrying out the obligation to make a living on a religious path, earning a living or entrepreneurship in a religious way.Keywords: Islamic entrepreneurship, Student's Cooperative Education and Management